1997
DOI: 10.1074/jbc.272.51.32136
|View full text |Cite
|
Sign up to set email alerts
|

Depression of T-cell Epitope Generation by Stabilizing Hen Lysozyme

Abstract: Conformational stability of proteins is an important factor that determines their resistance/susceptibility to proteolytic digestion. Intracellular proteolysis is the key step in antigen presentation events for protein antigens; hence, it is likely that increasing protein stability reduces the antigenicity of proteins. We prepared three hen egg white lysozyme derivatives possessing different stabilities by chemical modification to clarify the relationship between conformational stability and the antigenicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 56 publications
7
62
0
Order By: Relevance
“…1-15 CL-HEL . 35-108 HEL (18). Thus, the IgG production results were consistent with the T cell-stimulating capacities of the HEL derivatives.…”
Section: Immunogenicity Of Modified Lysozymessupporting
confidence: 73%
See 3 more Smart Citations
“…1-15 CL-HEL . 35-108 HEL (18). Thus, the IgG production results were consistent with the T cell-stimulating capacities of the HEL derivatives.…”
Section: Immunogenicity Of Modified Lysozymessupporting
confidence: 73%
“…Because protein unfolding may be a crucial step in intracellular Ag processing, the conformational stability of the protein Ag is important in determining the immune response. In a previous study using modified hen egg white lysozyme (HEL), we found that the T cell-triggering response and, therefore, the immune response, were governed by the degree of conformational stability of the protein Ags (18,19). This finding was supported by a study using derivatives of snake toxin with different stabilities, which found that Ag presentation was controlled by the stability of the toxin (20).…”
supporting
confidence: 63%
See 2 more Smart Citations
“…It has been reported that some enzymes and toxins are inactivated by mechanisms involving either oxidation of specific amino acids and formation of disulfide bonds after periodate and formaldehyde treatments [40][41][42]. In addition, some authors have described that increasing protein conformational stability might either increase [17] or diminish the immunogenicity of certain antigens [43][44][45]. The question that arises is why Ox-CCH presents higher immunogenicity than CCH.…”
Section: Discussionmentioning
confidence: 99%